Factors Influencing Utilization of Intra-Uterine Device among Postpartum Mothers at Gombe Hospital, Butambala disrtict, Uganda - Omona, Kizito; Namuli, Winnifred (Cogent medicine, 2020)
The most effective modern family planning method is long-acting reversible contraceptives (LARCs), including intra-uterine contraceptive devices (IUCD). It has multiple advantages over other reversible methods. Despite all known advantages of IUCD, its uptake is still low in Uganda. The purpose was to determine the factors influencing the utilization of intra-uterine contraceptive device among postpartum mothers. A facility-based cross-sectional analytical design was used. 202 Postpartum mothers were sampled and interviewed. Key informants interviews and FGDs were held. Out of 202 post-partum mothers, the prevalence of IUCD utilization was low at 16.3%. Knowledge level at was 55.9%. Education of mothers significantly influenced utilization (X2(3) = 28.22, p = <0.001) with primary education and secondary education being 10 times more likely (COR = 9.67, 95%CI (2.639–35.411)) and 6 times more likely (COR = 6.17, 95%CI (2.234–17.023) to influence IUCD utilization, respectively. Occupation of mothers also influenced utilization (p < 0.000). Most of the mothers were skilled laborers and yet they were less likely to utilize IUCD compared to non-skilled counterparts (COR = 0.19 95%CI: 0.082–0.431). Culture influenced utilization of IUCD (X2(1) = 18.22, p = 0.007). Healthcare providers should build the capacity of community health workers to promote effective community awareness about IUCD and its advantages. This will increase uptake.
Keywords: contraceptive utilization; post-partum mothers; intra-uterine contraceptive devise (IUCD